Effects of fat content of high-protein milk replacer on intake and growth performance of Holstein calves in summer and winter - R. Fukami; N. Kobayashi; K. Murayama; M. Oba; T. Sugino (Journal of Dairy Science)
ABSTRACT: The objective of this study was to evaluate the effects of fat content of high-protein milk replacer on intake and growth performance of dairy calves in summer and winter. Eighty-four Holstein heifer calves (BW at 7 d of age, 42.2 ± 2.54 kg; mean ± SD) were assigned to 1 of the 3 treatments: milk replacer containing 21% fat (LF; 4.7 Mcal of ME/kg), 26% fat (MF; 5.0 Mcal of ME/kg), and 32% fat (HF; 5.3 Mcal of ME/kg) on a DM basis (n = 14 each for summer and winter). Milk replacers were offered at 600 g/d (powder basis; 3.6 L/d) from 8 to 14 d, increased up to 800 g/d (4.8 L/d) from 15 to 21 d, 1,200 g/d (7.2 L/d) from 22 to 42 d, decreased down to 800 g/d (4.8 L/d) from 43 to 49 d, and 600 g/d (3.6 L/d) from 50 to 56 d, then weaned at 56 d of age. Data and samples were collected until 91 d of age. All the calves were fed a calf starter and chopped hay ad libitum from 7 d of age. In summer, HF group had lower starter intake than LF and MF groups during 51 to 56 d of age, whereas the HF treatment did not decrease starter intake in winter. These results are consistent with a tendency of interaction between treatment and season for body circumference gain during 43 to 56 d; HF group had lower body circumference gain than LF and MF groups in summer but not for winter. In addition, we found a trend for an interaction between treatment and season for withers height gain during 8 to 21 d; withers height gain in winter increased linearly as fat content of milk replacer increased but not for summer. These results suggested that increasing fat content of milk replacer increases growth performance of dairy calves in the early age, and does not decrease starter intake during the weaning transition in winter, whereas it decreases starter intake in summer.